Factorial Study to Evaluate the Individual and Combined Effects of Cyclodextrins and Tween 80 on the Solubility and Dissolution Rate of Aceclofenac - Chowdary, K.P.R.; Sudhakar Babu, A.M.S. (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate the individual main effects and combined (or interaction) effects of two cyclodextrins [ b-cyclodextrin (bCD) and hydroxypropyl-b-cyclodextrin (HPbCD)]2 factorial experiments. The solubility of aceclofenac in purified water (1), water containing 5 mM of cyclodextrins ( containing 5 mM of CDs ( factorial design. The individual and combined effects of enhancing the solubility of aceclofenac were highly significant ( aceclofenac was markedly enhanced by fold) individually as well as combindly by fold). Solid inclusion complexes of aceclofenac-cyclodextrins ( with and without Tween 80 as per 2 of aceclofenac from the cyclodextrin complexes prepared was studied in phosphate buffer of pH 6.8 (n = 4). Cyclodextrins alone gave higher enhancement in the dissolution rate and DE aceclofenac. The individual main effect of cyclodextrins ( effect of cyclodextrins and Tween 80 in enhancing the dissolution rate and DE significant ( a combination of solubility and dissolution rate of aceclofenac. bCD or HPbCD) (a), water containing 2 % Tween 80 (b) and waterbCD or HPbCD) and 2 % Tween 80 (ab) were determined as per 22bCD, HPbCD and Tween 80 inp < 0.01). The solubility ofbCD (1.57 fold), HPbCD (1.47 fold), Tween 80 (7.91bCD-Tween 80 (10.54 fold) HPbCD-Tween 80 (11.96bCD or HPbCD) were prepared2 factorial design by kneading method. The dissolution rate15 ofbCD and HPbCD) and the combined15 were highlyp < 0.01). Whereas the main effect of Tween 80 was not significant (p > 0.05). Thus,bCD-Tween 80 and HPbCD-Tween 80 is recommended for enhancing the and Tween 80, a surfactant on the solubility and dissolution rate of aceclofenac in a series of 2